The Effect of Indium Concentration on the Structure and Properties of Zirconium Based Intermetallics: First-Principles Calculations - Fuda Guo; Junyan Wu; Shuai Liu; Yongzhong Zhan (Advances in Condensed Matter Physics)
The phase stability, mechanical, electronic, and thermodynamic properties of In-Zr compounds have been explored using the first-principles calculation based on density functional theory (DFT). The calculated formation enthalpies show that these compounds are all thermodynamically stable. Information on electronic structure indicates that they possess metallic characteristics and there is a common hybridization between In-p and Zr-d states near the Fermi level. Elastic properties have been taken into consideration. The calculated results on the ratio of the bulk to shear modulus (B/G) validate that InZr3 has the strongest deformation resistance. The increase of indium content results in the breakout of a linear decrease of the bulk modulus and Young’s modulus. The calculated theoretical hardness of α-In3Zr is higher than the other In-Zr compounds.